2019
DOI: 10.1039/c8ta11058a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of covalent organic frameworks via in situ salen skeleton formation for catalytic applications

Abstract: A facile synthesis of COF-salen via in situ salen skeleton formation under air atmosphere is described herein. COF-salen–M prepared via metal ion coordination could efficiently catalyse chemical reactions, e.g. styrene epoxidation, epoxide hydration and cycloaddition reactions of epoxides with CO2. More interestingly, both cooperation and isolation effects were observed in COF-salen–M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 61 publications
4
90
0
Order By: Relevance
“…Another example of a salen-based COF was reported by Yang and co-workers in 2019. 122 Here, they developed an in situ salen formation method during the COF synthesis. In both cases, achiral salen-based monomers were used, and the resulting COFs showed high activity and stability as heterogeneous catalysts.…”
Section: Direct Synthesis From Achiral Skeleton Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of a salen-based COF was reported by Yang and co-workers in 2019. 122 Here, they developed an in situ salen formation method during the COF synthesis. In both cases, achiral salen-based monomers were used, and the resulting COFs showed high activity and stability as heterogeneous catalysts.…”
Section: Direct Synthesis From Achiral Skeleton Monomersmentioning
confidence: 99%
“…Wang et al utilized achiral salen ligands as building blocks to construct COF materials for efficiently catalyzing the Henry reaction 121 and Yang et al reported the synthesis of a salen-based achiral COF for cycloaddition reactions of epoxides with CO 2 . 122 After exchanging Zn 2+ ions for other metal ions of Zn(salen)based CCOFs (CCOF 4), the M(salen)-based CCOFs (4-M, Mn + = Cr 2+ , Co 2+ , Mn 2+ , Fe 2+ , V 4+ ) are proved to be efficient heterogeneous catalysts for asymmetric cyanation of aldehydes, Diels-Alder reaction, alkene epoxidation, epoxide ring-opening, and related sequential reactions. The 4-V promoted cyanation of aldehydes with TMSCN gave 89-94% ee of cyanohydrin silyl ethers.…”
Section: Asymmetric Catalysismentioning
confidence: 99%
“…The TEM and SEM images showed that all CNTs@POP‐Co(salen)‐n materials had almost identical core‐shell nanostructure and shell thickness to corresponding CNTs@POP‐salen‐n samples (Figure S3). The BET surface area of CNTs@POP‐Co(salen)‐n decreased in comparison to CNTs@POP‐salen‐n, possibly due to the occupation of Co cations in the polymer (Figure S4) …”
Section: Resultsmentioning
confidence: 99%
“…The BET surface area of CNTs@POP-Co(salen)-n decreased in comparison to CNTs@POP-salen-n, possibly due to the occupation of Co cations in the polymer ( Figure S4). [49] The catalytic performance of CNTs@POP-Co(salen)-1 was tested in the hydration of propylene oxide (PO) with H 2 O/PO molar ratio of 2 at 40°C ( Table 2 and Figure 4). The control experiments with CNTs as catalyst only afforded 9 % yield of 1,2-propanediol and no product was observed with CNTs@POPsalen-1 as catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…[27,28] Recently, porous COFs have been not only defined as splendid sorbents for a variety of gases, especially CO 2 , [29][30][31] but also applied as late-model of heterogeneous catalysts for different reactions. [32][33][34] To date, some COF-based heterogeneous catalysts for CO 2 cycloaddition reactions have been reported, [35][36][37][38][39][40][41][42] while it is still a great challenge to design COFs systems that can catalyze CO 2 conversion under mild and co-catalyst free conditions. As we know, the post-modified approach is a feasible approach to embellish targeted functional sites into the parent skeleton of COFs.…”
Section: Introductionmentioning
confidence: 99%